Annual organic matter dynamics in a small temperate mountain stream - Ferreira, Verónica (2013)
Temperate streams flowing through deciduous forests derive most of their energy and carbon from allochthonous organic matter supplied by the riparian vegetation mostly during the autumnal litter fall. The decomposition of this coarse particulate organic matter (CPOM) supports the aquatic foodwebs throughout the year. During the decomposition process, part of the CPOM is converted into fine particulate organic matter (FPOM). In this study, we assessed the relationships among decomposition rates of a dominant litter species, oak leaf litter (estimated by the litter bag approach in the presence and absence of macroinvertebrates), benthic CPOM stock and FPOM flux over 12 months in a temperate mountain oligotrophic stream. We also assessed the relationship between these organic matter variables and environmental variables over the same period. As expected from the seasonality in temperature, litter decomposition rates varied over the year and were positively correlated with water temperature and dissolved phosphorus concentration. However, benthic CPOM stock did not significantly change over the year; the higher rainfall in winter and the higher litter decomposition in spring might have compensated for each other in keeping the CPOM stock fairly constant year round. FPOM flux was positively correlated with litter decomposition rates as expected, and this relationship was primarily driven by the activities of detritivores and not of microbes. We can anticipate changes in the carbon cycle, both locally and downstream, if oligotrophic montane streams are subjected to temperature increases (e.g., due to removal of riparian vegetation or in a global warming scenario) and nutrient enrichment from effluents or agricultural activities.